ChemInform Abstract: Facile Three‐Component Synthesis and Insecticidal Evaluation of Hexahydroimidazo[1, 2‐a]pyridine Derivatives. Issue 23 (June 2015) - Fan, Ye‐Feng; Zhang, Wen‐Wen; Shao, Xu‐Sheng; Xu, Zhi‐Ping; Xu, Xiao‐Yong; Li, Zhong
Abstract A series of new hexahydroimidazopyridine derivatives is synthesized and evaluated for its activity against cowpea aphids.